Long-term cardiovascular safety of psychostimulants in children with attention deficit hyperactivity disorder. (3rd April 2019) - Conzelmann, Annette; Müller, Stefan; Jans, Thomas; Trott, Götz-Erik; Keil, Thomas; Gerlach, Manfred; Renner, Tobias J.
Abstract: Objective: Side effects are a concern during psychostimulant treatment. Unfortunately, many previous studies only investigated short-term effects of psychostimulants in laboratory settings which lack clinical daily routines. Methods: We examined 1042 patient records of patients with attention deficit hyperactivity disorder (ADHD) who were referred to a pediatric-psychiatry practice over 12 years. Data analysis was based on 466 children with ADHD who were newly treated with psychostimulants and who were not in treatment for elevated blood pressure. We analysed blood pressure percentiles, heart rate and BMI percentiles. Results: There was a decrease in systolic and diastolic blood pressure percentiles. Heart rate was not affected. BMI slightly declined in girls. Conclusions: In general psychostimulants were safe. To further elucidate negative effects of psychostimulants, long-term controlled and randomized studies in naturalistic settings are of interest.